Temperature‐ and Pressure‐Induced Switching of the Molecular Spin State of an Orthorhombic Iron(III) Spin‐Crossover Salt. Issue 5 (19th December 2012) - Tissot, Antoine; Shepherd, Helena J.; Toupet, Loic; Collet, Eric; Sainton, Joelle; Molnár, Gabor; Guionneau, Philippe; Boillot, Marie‐Laure
Abstract: The [(TPA)Fe III (TCC)] + complex [TPA = tris(2‐pyridylmethyl)amine, TCC 2– = 3, 4, 5, 6‐tetrachlorocatecholate dianion] forms a molecular solid with the SbF6 – anion, which exhibits an incomplete S = 1/2 ↔ S = 5/2 thermal spin‐crossover process centered at 250 K. Single‐crystal X‐ray diffraction, Raman spectroscopy, and magnetic measurements of this orthorhombic polymorph were performed to delineate the spin‐state thermo‐ and piezoswitching in relation to the structural and elastic properties. Indeed, a pressure‐induced spin crossover (centered at P 1/2 ≈ 1.65 kbar, T = 294 K) concomitant with unit‐cell contraction was observed by applying a hydrostatic pressure to the single crystal. Under ambient conditions, the piezo‐induced transition, like that induced thermally, is relatively gradual, which probably reflects a similar mechanism in response to both stimuli. Except for a 47 K shift, the spin‐crossover curves of the isostructural SbF6 – and PF6 – salts compare well. They are discussed with respect to structural anisotropy and pressure effects. Abstract : The spin‐state switching of [(TPA)Fe(TCC)]SbF6 [TPA = tris(2‐pyridylmethyl)amine, TCC 2– = 3, 4, 5, 6‐tetrachlorocatecholate dianion] is investigated under stimulation by temperature or pressure. Both processes follow the same structural mechanism and are compared to those observed for the PF6 – salt.